Legal Policies for Eradicating Criminal Acts of Domestic Violence - Husin Wattimena; Muis Pikahulan (Istinbath : Jurnal Hukum, 2024)
This study is about a legal study of the enforcement of Law No. 23 of 2004 concerning the elimination of domestic violence. It is described and analyzed more deeply on the principle of equality of law, for handling cases of domestic violence, the implementation of equality before the law, and models of legal protection. justice for perpetrators and victims of violence. In addition, this study aims to examine appropriate legal service procedures as well as legal protection for victims and perpetrators of crimes of domestic violence. On the other hand, there are cooperative efforts to recover victims of domestic violence based on Ministerial Regulation No. 4 of 2006 concerning the implementation and cooperation in the recovery of victims of domestic violence. The most important essence is the eradication of criminal acts of violence in the household which aims to make the conflicting parties aware in the home to be able to foster household integrity which affects children and people around the family. The method used in this study is empirical juridical and is described using primary and secondary data sources with literature review techniques using primary legal materials, secondary legal materials and tertiary legal materials. The primary legal material is in the form of applicable laws and regulations. With this study, it is hoped that the best system solution for handling cases of domestic violence in Indonesia will be obtained.